HUBUNGAN STATUS GIZI IBU HAMIL DENGAN BERAT BADAN LAHIR BAYI DI RSUD DR. MOEWARDI SURAKARTA - Permatasari , Ayu Dian (2008)
Mother and infant mortality rate also the raising of baby with low birth weight number after all fixed by pregnant nutritient states. Pregnant mother with malnutrition or cronical energy less disposed to have a baby with low birth weight who faced bigger mortality risk than a baby from a normal weight pregnant. Objective of this research are to know correlation between regnant mother nutrient states based on totally increased pregnant weight with baby birth weight at general territory hospital dr. Moewardi Surakarta. Descriptive analytic, from September until November 2008, using purposive sampling. The number of sampel are 98 pregnant mother who have birth in general territory hospital dr. Moewardi Surakarta at 2007. Statistic test using chi cuadrat program SPSS 15. Result obtained there were significant correlation between nutrition states of pregnant with baby birth weight. The conclusion is there were significant correlation between nutrition states of pregnant with baby birth weight in general territory hospital dr. Moewardi Surakarta.